Evaluation of an inexpensive needle test for the diagnosis of phosphorus deficiency and management of phosphorus supplementation for cattle: A multiple case study - Malafaia, Pedro; Garcia, Felipe Z.; Lopes, Samara P.; Souza, VinÍcius C.; Canella Filho, Camillo F.c.; Costa, Diogo F.a.; Veiga, Cristiano C.p. (Academia Brasileira de Ciências, 2018)
ABSTRACT The needle test (NT) is a point-of-care test developed in Brazil to evaluate the Phosphorus (P) status in cattle. Based on bone resistance, the NT is a very inexpensive method which allows the diagnosis of any degree of P deficiency in a fast and simple way in vivo and directly on farm. The NT measures three levels of resistance in the transverse process (TP) of the lumbar vertebrae: a) TP that are impenetrable and result in warping of the needle (P healthy animals); b) TP offering some resistance to the penetration (animals with subclinical P deficiency); and c) TP which has minimal resistance to penetration (clinical P deficiency). This manuscript presents results from a series of case studies to evaluate the hypothesis that the NT could be used to assess P status in cattle and assesses the usefulness of results to support decision making on mineral supplementation strategies for grazing cattle. The NT was able to detect the changes in the resistance patterns of the TP, as there was reduction or elevation of P levels in the mineral mixtures. The NT was useful to assist in decision-making for adoption of mineral supplementation strategies better suited for each farm, helping farmers to save money and avoid unnecessary waste of P.
Keywords: Beef and dairy cattle; Phosphorus; mineral deficiency; mineral supplementation